The Role of Motor Activities in Shaping the Personality of Kindergarten Children - Sohaila Azzam; Mostafa Sadek; Masoud Gharaba,; Fatma Naji (International Journal of Instructional Technology and Educational Studies)
The present study aims to explore the role of motor activities in fostering the personality development of kindergarten children. Additionally, it seeks to propose a framework to enhance the effectiveness of motor activities in this developmental context. To achieve this, the researcher employed a descriptive-analytical methodology, selecting a stratified random sample consisting of 589 kindergarten teachers. A structured questionnaire comprising 59 items was administered. The findings indicated that motor activities play a significant role in the personality development of kindergarten children, as perceived by the female teachers, with a relative weight of 63.97%. The study culminates in a set of recommendations aimed at optimizing the role of motor activities in enhancing various aspects of the child's personality